137k views
1 vote
2x−5 = 3 (1−x)+22?
is x=6?

User Cheny
by
5.4k points

2 Answers

5 votes

Answer:

x=6

Explanation:

You are correct. x does equal 6

User Michal Palczewski
by
5.4k points
0 votes

Answer:

Yes

x = 6

Explanation:

Given

2x - 5 = 3(1 - x) + 22

First distribute 3 into (1 - x)

We have

2x - 5 = 3 x 1 -3 x X + 22

2x - 5 = 3 - 3x + 22

The expression can be rearranged as

2x - 5 = 3 + 22 - 3x

2x - 5 = 25 - 3x

Add 3x to both sides

3x + 2x - 5 = 25 - 3x + 3x

5x - 5 = 25

Add five to both sides

5x - 5 + 5 = 25 + 5

5x = 30

Divide both sides by 5

5x/5 = 30/5

x = 6

User Pete Rossi
by
6.2k points